The ILO's maritime labour convention - Wang, Xujie. (2011)
As a unified standard providing wide coverage on seafarers’ rights and decent working conditions, MLC 2006 is expected to have far reaching impacts on the global maritime industry. Although it is regarded as the “fourth pillar” of the international regulatory regime along with MARPOL, SOLAS and STCW, the role MLC 2006 will play is much more important since it is the only convention dealing with the crew’s conditions on board. Being at the forefront of the global maritime industry and a world renowned port, Singapore will definitely be affected by the implementation of MLC 2006 in various ways. Therefore, it is of crucial importance for the shipping industry in Singapore to appreciate the potential impact of implementation of this convention.